Critical Dimensions Of Service Satisfaction In Virtual Environments: An Importance-Performance Analysis - Meirani Harsasi; Moh. Muzammil; Faridah Iriani (EKOMBIS REVIEW: Jurnal Ilmiah Ekonomi dan Bisnis, 2026)
Much attention has been paid by scholars to measuring student satisfaction, especially in the online environment since it is related to the quality of the learning process and student performance. This study has the main objective of analyzing student satisfaction in online learning by considering the level of importance of elements in online learning. This research employed a simple random sampling method and succeeded in obtaining 391 data. To answer the desired research objectives, the Importance Performance Analysis (IPA) approach was chosen to find out which aspects need to be improved in online learning. The research results show that three attributes have the lowest performance values, namely the use of online learning platforms for various forms of learning resources, information about online learning, and ease of use of the LMS platform. These results have implications for policymaking and these three elements need to be prioritized for improvement. This study provides strong theoretical and practical support for improving online learning in terms of important aspects that support student satisfaction